Marga Saibatin Desa Sukamakha: Sejarah, Struktur, Tradisi, Kewajiban, Kekhasan dalam Hukum Adat - Diani, Deva; Agustine, Yolanda Fatima; Nurholisah, Febri Hana; savana, Elsa Aura; Halim, Abdul; Manurung, Yosia Agustant Parulian (Penerbit Goodwood, 2024)
Purpose: This research describes the social organization, customary practices, and traditional values of the Marga Way Lima community in Pekon Sukamara, Bulok District. It also examines how the community preserves its cultural heritage and social order amid modern societal changes. Methodology/approach: Using an empirical approach, data were collected through field observations, in-depth interviews with traditional leaders such as Punyimbang, Batin, and Dalom, and documentation of ongoing traditions. Data were analyzed systematically to identify patterns and mechanisms sustaining social structures and cultural values despite modernization. Triangulation ensured data validity, reflecting real field conditions. Results/findings: The Marga Way Lima community maintains a complex social hierarchy led by Punyimbang, Batin, and Dalom. They actively preserve cultural ceremonies like Nayuh, Bujang Gadis, Rudat Dance, Kesegh Dance, Betabuh, and Sekuaghian. Core principles such as piil pesenggiri, nemui nyimah, and Sakai sambayan are central to rituals. Oral traditions and warahan practice remain vital to protecting their historical legacy and identity. Conclusions: The community has maintained its social structure and Sai Batin values despite modernization. Traditional leaders and cultural practices play key roles in sustaining identity and social solidarity, acting as adaptation and resistance to cultural homogenization. Limitations: The study is limited to Pekon Sukamara and relies on oral histories due to scarce written records, limiting broader applicability. Contribution: This research offers insights into customary law, anthropology, and cultural studies, aiding policymakers and stakeholders in cultural heritage conservation.